Association of decreased triadin expression level with apoptosis of dopaminergic cells in Parkinson’s disease mouse model - Min Hyung Seo (BMC, 2021)
Abstract Background Parkinson’s disease (PD) represent a loss of dopaminergic neurons in the substantia nigra (SN) of the midbrain. However, its cause remains unknown and Triadin (TRDN) function in the brain is also unknown. To examine the relationship between TRDN and PD, the expression levels of protein related to PD in TRDN knockdown status were studied in the SH-SY5Y cells. Cell viability and apoptosis were assessed to examine the apoptosis effect on dopaminergic cells by decreased TRDN, and the levels of the proteins related to apoptosis were also confirmed. Results This study confirmed decreased TRDN expression level (P < 0.005) at the SN in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-induced PD mouse model and identified the functional features of TRDN. Our results showed a relationship between TRDN expression and PD in that reduced TRDN level induced PD-like characteristics. Interestingly, there was TRDN expression in the regions where dopaminergic cells are in the SN, and the expression patterns of TRDN and tyrosine hydroxylase (TH) were similar. Decreased TRDN level also induced apoptotic characteristics and the Fluorescence-activated cell sorting analysis results showed that apoptosis increased (P < 0.05) as the TRDN small interfering RNA concentration increased. The cytotoxicity assay revealed that cell viability also decreased (P < 0.0005) in the same condition as that in the Fluorescence‐activated cell sorting analysis. Conclusions Decreased TRDN level could be related with the apoptotic death of dopaminergic cells at the SN in PD, and TRDN administration could give a positive effect on PD by reducing apoptotic cell death.